2022
DOI: 10.1002/elps.202100374
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of U87 glioma cells by dielectrophoresis

Abstract: Glioblastoma multiforme is the most aggressive and invasive brain cancer consisting of genetically and phenotypically altering glial cells. It has massive heterogeneity due to its highly complex and dynamic microenvironment. Here, electrophysiological properties of U87 human glioma cell line were measured based on a dielectrophoresis phenomenon to quantify the population heterogeneity of glioma cells. Dielectrophoretic forces were generated using a gold‐microelectrode array within a microfluidic channel when 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Next, the low conductive DEP buffer consisting of 8.6% sucrose (BioFroxx, Hesse, Germany), 0.3% glucose (Sigma Aldrich, St. Louis, MI, USA), and 0.1% Bovine Serum Albumin (BSA, PAN-Biotech, Bayern, Germany) was prepared in deionized water. The conductivity value of the suspension was set to 20 µS/cm verified by measuring a conductivity meter (CORNING, 311 Conductivity, Merck KGaA, Darmstadt, Germany) [ 43 , 44 ]. Afterwards, glioma cells were spun down at 3000 rpm (Hettich EBA 20 Centrifuge, Merck KGaA, Darmstadt, Germany) for 5 min to wash the cells using the DEP buffer twice.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, the low conductive DEP buffer consisting of 8.6% sucrose (BioFroxx, Hesse, Germany), 0.3% glucose (Sigma Aldrich, St. Louis, MI, USA), and 0.1% Bovine Serum Albumin (BSA, PAN-Biotech, Bayern, Germany) was prepared in deionized water. The conductivity value of the suspension was set to 20 µS/cm verified by measuring a conductivity meter (CORNING, 311 Conductivity, Merck KGaA, Darmstadt, Germany) [ 43 , 44 ]. Afterwards, glioma cells were spun down at 3000 rpm (Hettich EBA 20 Centrifuge, Merck KGaA, Darmstadt, Germany) for 5 min to wash the cells using the DEP buffer twice.…”
Section: Methodsmentioning
confidence: 99%
“…The DEP chip consists of 65 pairs of electrodes in an interdigitated organization to generate a non-uniform electric field. The gold electrodes were fabricated at 40-nm height, 1.8-mm length, and 60-µm width using the lift-off process as detailly reported by Sengul et al [ 44 ], Figure 1 A. We used a cutting plotter machine (Graphtech CE6000-40, Yokohama, Japan) to create a 100-µm thick microfluidic channel on the electrode array using a double-sided pressure-sensitive adhesive sheet (PSA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that U87 MG is a highly sensitive brain cancer cell line [ 159 ]. Recent studies have suggested that cold plasma plays a significant role in U87 MG [ 160 ], specifically via the total mitogen-activated protein kinase (MAPK) signaling pathway [ 140 , 158 ] without affecting normal cells.…”
Section: Biological Effects Of Microwavesmentioning
confidence: 99%